The Essence of the Development of Professional Mobility of Future Educators in Higher Education Institutions - Shakhnoza, Abdukarimova (International Journal on Integrated Education, 2023)
From this point of view, in the development of the professional mobility of the future teacher in higher education institutions, a modern teacher should not only use his professional skills, high level of qualification, but also his intellect, active participation in innovative processes, quick information retrieval, processing, mobility and it is necessary to be the initiator. These requirements determine the need for pedagogues to continuously study, develop their knowledge, quickly adapt to changes and make decisions, develop their mission and develop professional mobility that expresses their constant activeness.